Hemoglobin, Physical Activity, and Sleep Quality as Protective Factors of Common Mental Disorder Among University Students - Akmal Novrian Syahruddin; Fitriyah Amiruddin; Diana Mirja Togubu; Novi Puspita Sari; Elisabeth Milka; Priskilia Putri (Universitas Sulawesi Barat, 2026)
The prevalence of common mental disorders (CMD) among university students is increasing. Globally, one in seven people (1.1 billion) lived with a mental disorder, and 15% of the population including adolescents and adults were affected. These growing burdens highlight the importance of examining lifestyle and hematological factors related to CMD. This study aims to examine the associations of hemoglobin (Hb) levels, physical activity, and sleep quality with CMD. In this cross-sectional study, 105 active students from Tamalatea University, Makassar, were selected through proportional stratified sampling. Data included demographics, anthropometry, total weekly physical activity via the International Physical Activity Questionnaire–Short Form (IPAQ-SF), sleep quality via the Pittsburgh Sleep Quality Index (PSQI), Common Mental Disorder (CMD) symptoms via the Depression, Anxiety and Stress Scales (DASS-42), and hemoglobin (Hb) levels. Multiple logistic regression was used for data analysis. After covariate adjustment, moderate (aOR=0.17; 95%CI: 0.04–0.70; p=0.014) and high physical activity (aOR=0.08; 95%CI: 0.01–0.56; p=0.011) were significantly associated with lower odds of CMD compared with low activity. Good sleep quality was also protective (aOR=0.15; 95%CI: 0.03–0.76; p=0.022). Higher hemoglobin levels showed a borderline protective association (aOR=0.64; 95%CI: 0.41–1.00; p=0.050). Age, gender, BMI, and allowance were not significant predictors in the final model. Moderate to high physical activity, good sleep quality, and higher hemoglobin levels are protective factors against CMD among university students. These findings support the implementation of lifestyle based promotional strategies and hematological status monitoring within the campus setting.